Development of a Google for Education-Based Digital Module to Improve Students' Critical Thinking in Islamic Religious Education Learning - Diantika Rahmat Galih Permana; Syarip Hidayat; Heri Yusuf Muslihin (GoAcademica Research & Publishing, 2026)
The integration of digital technology in education has become increasingly important to foster students’ critical thinking skills, particularly in Islamic Education (PAI), where conventional teacher-centered approaches often limit active engagement and higher-order thinking. This study aims to analyze the development and implementation of a Google for Education-based digital module designed to enhance students’ critical thinking skills in PAI learning at Public Elementary School (SDN) Indihiang. A qualitative research approach was employed, utilizing interviews, classroom observations, and document analysis to explore the effectiveness of the digital module and its impact on student learning. The module was developed by integrating various Google for Education tools, including Google Classroom, Google Slides, Google Forms, and interactive hyperlinks, to provide accessible and interactive learning experiences. The findings indicate that the digital module effectively promotes students’ critical thinking by encouraging them to formulate analytical questions, provide logical reasoning, compare concepts, and solve contextual problems related to Islamic Education content. Furthermore, the implementation of the module supports independent learning and fosters active collaboration among students. The study concludes that Google for Education-based digital modules can serve AS an innovative learning medium that improves the accessibility, flexibility, and clarity of instructional content while strengthening students’ critical thinking competencies and supporting the development of 21st-century learning skills in primary education.